THE PHENOMENON OF FLEXING BEHAVIOUR ON SOCIAL MEDIA EFFECTS ON COLLEGE STUDENTS’ PERSONALITY - Raihana Sakdiyah; Alemina Br. Perangin-angin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Flexing is a term or slang that defines the conduct of excessive self-promotion when someone is displaying something. This might include the practice of often releasing information after acquiring a new item, the technique of constantly sharing successes on social media or the behaviour of frequently uploading vacation photographs. The qualitative research in this study, which adopts a grounded theory technique, focuses on the flexing behaviour demonstrated by college students as participants. This study aims to